Chemical constituents and bioactivities of Glinus oppositifolius - Ragasa, Consolacion Y. (Animo Repository, 2015)
Objectives: To isolate the secondary metabolites from the dichloromethane (DCM) extracts of Glinus oppositifolius; to test for the cytotoxicity of a new triterpene, oppositifolone (1); and to test for the hypoglycemic, analgesic, and antimicrobial potentials of 1, DCM and aqueous leaf extracts of G. oppositifolius. Methods: The compounds were isolated by silica gel chromatography and identified by nuclear magnetic resonance spectroscopy. The cytotoxicity potential of 1 was tested using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Triterpene 1, DCM, and aqueous leaf extracts were tested for hypoglycemic potential using the oral glucose tolerance test; analgesic potential using the tail-flick assay, and antimicrobial potential using the disc diffusion method. Results: The DCM extracts of G. oppositifolius afforded 1, squalene, spinasterol, oleanolic acid, phytol, and lutein from the leaves; squalene and spergulagenin A from the stems; and spinasterol from the roots. Triterpene 1 was cytotoxic against human colon carcinoma 116 with an IC50 value of 28.7 but did not exhibit cytotoxicity against A549. The aqueous leaf extract at 200 mg/kg body weight (BW) exhibited hypoglycemic activity with a pronounced % blood glucose reduction of 70.76% ±17.4% within 0.5 h after introduction. The DCM leaf extract showed a lower % blood glucose reduction of 18.52% ±13.5% at 200 mg/kg BW within 1.5 h after introduction, while 1 did not exhibit hypoglycemic activity. The samples did not exhibit analgesic property and were inactive against multiple drug resistant bacterial pathogens. Conclusion: The compounds responsible for the hypoglycemic activity of G. oppositifolius which are fast acting (0.5 h) are found in the aqueous leaf extract. © 2015, Medical Knowledge. All rights reserved.